Environmental economics and sustainability - Lin, Brian Chi-ang; Zheng, Siqi (John Wiley & Sons, 2017)
Environmental Economics and Sustainability presents a collection of peer-reviewed research articles contributed by international experts that reveal the current state of our knowledge in the field of environmental economics. -Presents the latest research results on a plethora of issues relating to environmental economics and sustainability -Features original contributions from top experts in the field from around the world -Addresses several of the contemporary challenges of sustainability while infusing new energy into the field of environmental economics -Covers myriad topics relating to environmental economics and sustainability including climate change, air pollution, CO2 emissions, recycling, and the international environmental agreement.